Caring Perawat Berhubungan dengan Kesiapan Keluarga Menerima Informasi Kesehatan Terapi Lanjutan - Fitriyah, Cholifatul; Suminar, Ervi; Fitrianur, Widya Lita; Widiyawati, Wiwik (Fakultas Ilmu Kesehatan, 2023)
Caring is an important core part, especially in nursing practice and it is believed that caring behavior for clients and working with clients from various environments is the essence of nursing. One other side of nurse caring is the readiness of the patient's family to receive nurse information. This study aims to determine the relationship between caring for nurses and the readiness of the patient's family to receive health information about advanced therapy in the Mecca Room at Muhammadiyah Gresik Hospital. This study used a cross-sectional approach with a population of 41 patients who were treated in the Mecca room at Muhammadiyah Gresik Hospital. Purposive sampling technique with a sample of 37 people. Statistical test using Rank Spearman. The caring behavior of nurses in the Mecca Room at Muhammadiyah Gresik Hospital was mostly good and the readiness of the family to receive health information about further therapy was mostly (64.9%). The results of the Rank Spearman statistical test obtained a p value of 0.00 <α0.05. The correlation coefficient value was 0.720, which means that the level of relationship is strong. There is a significant relationship between nurse caring behavior and family readiness to receive health information on advanced therapy in the Mecca Room, Muhammadiyah Gresik Hospital